ESTIMATION OF GENETIC DIVERSITY OF PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) STRAINS FOUND IN DIFFERENT AREAS OF PAKISTAN USING RAPD AND 16S rRNA ANALYSIS - T. Shaheen; A. A. Khan; Mahmood-ur-Rahman; M. T. U. Qamar; M. Rahman (Journal of Animal and Plant Sciences, 2015)
The present study was an approach to provide the information about the diversity of rhizobacteria involved directly or indirectly in the plant growth and development. Among molecular markers, RAPD proved to be the most promising tool to delineate rhizobacterial strains. Seventeen bacterial strains of rhizobacteria were isolated from different parts of Pakistan (Sargodha, Mianwali, Karak and Faisalabad). RAPD analysis of these strains has shown a high degree of polymorphism. Range of genetic similarity was observed 0.543-0.927. Cluster analysis resulted into three clusters (I, II and III). Cluster I comprised of bacterial strains collected from Faisalabad, cluster II comprised of Strains collected from Sargodha while cluster III included strains from Mianwali. Strains isolated from the Karak region were not making any cluster. These results have shown that soil conditions and local environment has a significant impact on genetic make-up of bacterial strains. Further 16S rRNA analysis of the strain was performed to validate the results. Results of 16S rRNA analysis have revealed that most dominating species were Bacillus sp. and two strains were also showing homology with Brevibacterium halotolerans. The findings of this study were very promising for the application of PGPRs for plant growth improvement.
Keywords: Rhizobacteria; RAPD; Genetic diversity; Soil; 16S rRNA; Plant growth; Sequencing